Analysis of maternal and fetal outcome in twin pregnancy - N., Sunanda; R., Nikitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The use of fertility drugs, in-vitro fertilization, gestational age and other factors contribute to the rising incidence of multiple pregnancies. Multiple pregnancies are associated with increased risk of obstetric complications and perinatal mortality and morbidities. The present study analyzes maternal and perinatal outcomes in multiple pregnancies to identify associated complications and reduce risks. Methods: A retrospective study was conducted in the OBG department of MMCRI, from January 2023 to December 2023. Data from 182 twin deliveries were analyzed. All women diagnosed with twin pregnancies via clinical or ultrasound examination were included. Results: Of the 7598 deliveries recorded, 182 (3.72%) were twin deliveries. The mean maternal age was 27.32±4.5 years. Most twin pregnancies occurred in multigravida women (67.7%) and were conceived after ovulation induction (74.43%). Dichorionic twins (71.4%) were more common than monochorionic twins (19.54%). Spontaneous delivery occurred in 132 (71.4%) cases, while 28.6% were induced. The rate of LSCS was 34.67%, with the most common indication being first twin not being cephalic. Preterm labour (72.7%), anemia (42%) and hypertensive disorders (38%) and postpartum hemorrhage (14.33%) were the most common complications. Single fetal demise occurred in 10% cases 10%. Conclusions: Twin pregnancies are more common in advanced maternal age and often result from fertility treatments. Early diagnosis, vigilant prenatal and postnatal care and timely intervention can significantly reduce maternal and perinatal risks.